Identyfikacja wsadu w dwuczęstotliwościowym nagrzewaniu indukcyjnym - Urbanek, Piotr; Kucharski, Jacek (Wydawnictwo Politechniki Łódzkiej, 2013)
W pracy przedstawiono założenia dotyczące struktury i działania systemu określającego zdolność do nagrzewania wsadu przy założonym procesie technologicznym na stanowisku inteligentnego generatora dwuczęstotliwościowego. Opisano metody potwierdzania własności fizycznych nagrzewanego wsadu oraz otrzymywania doświadczalnego nowych informacji, które mogą być zapisane w postaci reguł w bazie wiedzy.

This paper presents the assumptions regarding the structure and operation of a system for determining the ability of the heating load at a given process in stand of an intelligent dual-frequency generator. The methods of physical confirmation and receiving an experimental data of new information that can be stored in the form of rules in the knowledge base have been also described.
Charge identification in dual-frequency induction heating